المفردات الاصطلاحية في كتاب توضيح مقاصد العقيدة الواسطية لشيخ الإسلام ابن تيمية - Ashar Nurdiansyah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2019)
This study aims to find out the terms of Islamic Aqeedah in the book of Taudhihi Maqashid Al-Aqidah Al-Wasithiyyah written by Syaikh Islam Ibnu Taymiah, and analyze these terms by presenting several examples of their methods of use to enrich the language repertory of STIBA Ar Raayah students, while reviving the heritage of Islamic language that is related to the terminology of Islamic Aqeedah, and also aims to develop curriculum that can facilitate the learning process in the field of Arabic language education. This study uses descriptive—analytic method, explicitly by inventorying the terms of Islamic Aqeedah in the book of Taudhihi Maqashid Al-Aqidah Al-Wasithiyyah Li Syaikhil Islam Ibnu Taymiah, thus analyzing those terms etymologically and terminology by referring to Arabic dictionaries and Aqeedah books. The results of this study conclude that there are Islamic Aqeedah terms in the book of Taudhihi Maqashid Al-Aqidah Al-Wasithiyyah Li Syaikhil Islam Ibnu Taymiah, and the total number of these terms reaches 84 words, and defines each term both etymologically and terminologically, hence describing several examples of the methods of use to enrich the language of STIBA Ar Raayah students.